2004
DOI: 10.1016/s0006-3207(03)00151-4
|View full text |Cite
|
Sign up to set email alerts
|

Is the western population of the European mink, (Mustela lutreola), a distinct Management Unit for conservation?

Abstract: The European mink (Mustela lutreola) is one of the most threatened carnivores in Europe, with fragmented populations in Belarus, Russia and Romania, as well in south-western France and northern Spain. Many populations have become extinct recently, or are declining. We investigated mitochondrial DNA variation, using the complete D-loop region, and concentrating on the west European population. The aim was two-fold: to use the genetic information to advise on the conservation of European mink, and to begin to un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
43
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(47 citation statements)
references
References 43 publications
(46 reference statements)
2
43
0
Order By: Relevance
“…The extremely low genetic diversity in G. glis suggests that this species may be vulnerable to rapid climatic shifts, as is thought to be the case for many other endangered species, such as mustelids (Michaux et al 2004), the Tasmanian devil (Sarcophilus harrisii- Jones et al 2004), and the cheetah (Acinonyx jubatus-O' Brien et al 1986). Future work examining other glirids for concordant patterns may reveal a link between hibernation behavior and population structure in this family, and these studies should have important implications for conservation of G. glis and other potentially threatened glirid species.…”
Section: Discussionmentioning
confidence: 99%
“…The extremely low genetic diversity in G. glis suggests that this species may be vulnerable to rapid climatic shifts, as is thought to be the case for many other endangered species, such as mustelids (Michaux et al 2004), the Tasmanian devil (Sarcophilus harrisii- Jones et al 2004), and the cheetah (Acinonyx jubatus-O' Brien et al 1986). Future work examining other glirids for concordant patterns may reveal a link between hibernation behavior and population structure in this family, and these studies should have important implications for conservation of G. glis and other potentially threatened glirid species.…”
Section: Discussionmentioning
confidence: 99%
“…Macdonald et al (2002) modelled the reintroduction of Mustela lutreola in Estonia using a preliminary population viability analysis to estimate the probability of successful establishment of the introduced population. They concluded that at least 30 to 40 founder animals are necessary to guarantee high genetic variability of a reintroduced population of M. lutreola originating from the eastern population, which has been verified as highly variable (Michaux et al 2004(Michaux et al , 2005. Based on the results of the aforementioned experimental reintroductions of M. lutreola, we released 48 animals over a 2 yr period in a nature reserve in Saarland as part of a larger release program (75 founder animals within a 3 yr period).…”
Section: Introductionmentioning
confidence: 99%
“…According to the most feasible hypothesis, the Spanish section was founded by French individuals whose origins come from Central Europe (Rodríguez de Ondarra, 1955, 1963de Bellefroid, 1999de Bellefroid, , 2005. The process of its arrival is, however, under discussion with currently two hypotheses: human introduction or natural invasion (Michaux et al, 2004(Michaux et al, , 2005. Nonetheless, there is a consensus on the fact that the entire Western population (Spain and France) is the result of a "bottleneck" effect that reduced the genetic variability of the population in the area (Michaux et al, 2004;2005).…”
Section: Introductionmentioning
confidence: 99%
“…The process of its arrival is, however, under discussion with currently two hypotheses: human introduction or natural invasion (Michaux et al, 2004(Michaux et al, , 2005. Nonetheless, there is a consensus on the fact that the entire Western population (Spain and France) is the result of a "bottleneck" effect that reduced the genetic variability of the population in the area (Michaux et al, 2004;2005). In Spain, the species is currently distributed along Navarra, La Rioja, Basque Country, Eastern Castilla y León (NW Burgos and North Soria) and Central Aragón (West Zaragoza) (González-Esteban et al, 2001;Palazón et al, 2003;Zabala et al, 2004) (Figure 2).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation